Teaching young multilingual learners : key issues and new insights - De Oliveira, Luciana C.; Jones, Loren (Cambridge elements. Elements in language teaching., 2023)
This Element provides an overview of research focusing on language teaching practices for young multilingual learners in primary classrooms in English-speaking contexts. The authors use the notion of culturally sustaining teaching practices to provide examples from pedagogy-informed research studies.